1987
DOI: 10.1002/j.1460-2075.1987.tb02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic fatty acylation of p21N-ras.

Abstract: To study the acylation of p21N‐ras with palmitic acid we have used cells which express the human N‐ras gene to high levels under control of the steroid‐inducible MMTV–LTR promoter. Addition of [3H]palmitate to these cells resulted in detectable incorporation of label into p21N‐ras within 5 min, which continued linearly for 30‐60 min. Inhibition of protein synthesis for up to 24 h before addition of [3H]palmitate had no effect on acylation of p21N‐ras, suggesting that this can occur as a late post‐translational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
203
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(220 citation statements)
references
References 47 publications
15
203
1
1
Order By: Relevance
“…Unlike myristoylation, palmitoylation of cysteine residues is a reversible modification. Pulse-chase experiments have demonstrated a fast turnover of palmitate group of several proteins, including H-ras and N-Ras [13], the transferrin receptor [14] and neuronal growth cone protein GAP-43 [15]. It is possible that this dynamic modification, like reversible phosphorylation, can regulate a variety of cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike myristoylation, palmitoylation of cysteine residues is a reversible modification. Pulse-chase experiments have demonstrated a fast turnover of palmitate group of several proteins, including H-ras and N-Ras [13], the transferrin receptor [14] and neuronal growth cone protein GAP-43 [15]. It is possible that this dynamic modification, like reversible phosphorylation, can regulate a variety of cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the slower rate, these data unambiguously demonstrate that SML is able to compete irreversibly, preventing GN from exchanging back in. This suggests that a covalent inhibitor may be able to overcome the endogenous pool of GDP/GTP within the cell due to the relatively long 14-to 24-h t 1/2 of Ras if appropriate dosing regimens can be developed that maintain exposure of G12C K-Ras to covalent inhibitors (32,33). We note that this assay method will be useful in developing inhibitors of K-Ras G12C with more "drug-like" characteristics, and it also may be applied to other protein targets for which cysteine-targeted irreversible therapeutics are being developed.…”
Section: Sml Efficiently Competes With Gtp and Gdp For Binding To G12mentioning
confidence: 99%
“…Mutagenesis of the H-Ras palmitoylated cysteines 181 and 184 revealed that H-Ras mono-palmitoylated on cysteine 184 is trapped within the Golgi complex; in contrast, mono-palmitoylation of cysteine 181 enables cell surface localisation [61]. Importantly, palmitoylation unlike farnesylation is labile with half-lives estimated to be a few minutes to a few hours depending on the methods used for analysis [62][63][64]. These are much shorter than the 21 hour half life of H-Ras meaning that palmitoylated Ras isoforms must go through many cycles of acylation and deacylation.…”
Section: Compartmentalisation Of Rasmentioning
confidence: 99%